2008
DOI: 10.1007/s10787-008-8039-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and anti-inflammatory activities of some isolated constituents from the stem bark of Allanblackia monticola Staner L.C (Guttiferae)

Abstract: Stem bark of Allanblackia monticola has been used in association with others plant in the Cameroonian folk medicine for the treatment of various diseases such amoebic dysentery, diarrhoea, lung infections, and skin diseases. The methylene chloride fraction, its isolated compounds like alpha-mangostin, lupeol and acid betulinic were screened for antioxidant activity using free radical scavenging method. These isolated compounds were further tested for anti-inflammatory properties using carrageenan-induced model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 23 publications
(22 reference statements)
2
47
0
1
Order By: Relevance
“…The significant anti-inflammatory activity observed for the ethanolic and the DCM fraction of O. elliptica could be attributed to a combination of the various phytochemicals detected viz; pentacyclic triterpenes, β-sitosterol glucoside and alkaloids. These results are in accordance with previous findings from the literature in which lupeol and lupeol acetate were reported to exhibit higher anti-inflammatory activity than indomethacin in rat and mouse models of inflammation [27,28]. Lupeol was reported to act as an anti-inflammatory agent with a mechanism similar to COX-selective inhibitor drugs [29], as well as, in-vitro inhibition of PGE2 and tumournecrosis factor-α [30].…”
Section: Table 4 Effects Of O Elliptica Extracts and Indomethacin Osupporting
confidence: 92%
“…The significant anti-inflammatory activity observed for the ethanolic and the DCM fraction of O. elliptica could be attributed to a combination of the various phytochemicals detected viz; pentacyclic triterpenes, β-sitosterol glucoside and alkaloids. These results are in accordance with previous findings from the literature in which lupeol and lupeol acetate were reported to exhibit higher anti-inflammatory activity than indomethacin in rat and mouse models of inflammation [27,28]. Lupeol was reported to act as an anti-inflammatory agent with a mechanism similar to COX-selective inhibitor drugs [29], as well as, in-vitro inhibition of PGE2 and tumournecrosis factor-α [30].…”
Section: Table 4 Effects Of O Elliptica Extracts and Indomethacin Osupporting
confidence: 92%
“…Bureeva et al (2009) have studied betulin disulfate and betulinic acid sulfate on the classical pathway of complement activation induced by ischemia, and showed that triterpenoids have inhibitory effects on complement activation. Furthermore Nguemfo et al (2009) using a free radical scavenging method, showed weak antioxidant activity for betulinic acid while they demonstrated the antiinfl ammatory properties of betulinic acid in the carrageenan-induced infl ammation model. However, more experiments are necessary to explain the structure/function relationship of triterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…(Nigam et al, 2007;Saleem, 2009) Anti-inflammatory (Nguemfo et al, 2009;Saleem, 2009 The same properties could also be produced by similar compounds from Dillenia species.…”
Section: Declaration Of Interestmentioning
confidence: 94%